2014
DOI: 10.17159/2413-3051/2014/v25i3a2661
|View full text |Cite
|
Sign up to set email alerts
|

The energy profile of a low-income urban community

Abstract: As part of a household energisation experiment, a baseline survey was undertaken from a sample of 152 households in the informal settlement of Samora Machel. The survey covered energy needs for cooking, space heating, water heating, lighting and any other demands, the costs of energy and total household monthly expenses. The average home had 3-4 inhabitants in less than 2 rooms. Paraffin was the primary source of energy for cooking and space heating, and played a significant role in water heating and lighting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…7 This study is similar in principle to the study carried out by Lloyd [8] in the Samora Machel resettlement area in Cape Town. Similarities and differences can be drawn from the results of the two surveys.…”
Section: Fuel Preferencesmentioning
confidence: 65%
See 4 more Smart Citations
“…7 This study is similar in principle to the study carried out by Lloyd [8] in the Samora Machel resettlement area in Cape Town. Similarities and differences can be drawn from the results of the two surveys.…”
Section: Fuel Preferencesmentioning
confidence: 65%
“…The use of multiple energy sources (energy stacking) in this area is an expected result. Similar studies found that lowincome households rely on multiple fuels to meet their basic energy needs [7,8,10,11]. According to Heltberg [7], this is often why introduction of a new fuel may not displace the fuels already in use.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations